Implementación de un sistema de control interno y su incidencia en la eficacia del órgano de contrataciones de la Red de Salud Trujillo, ejercicio 2017 - Miñano Vásquez, Pérsida Ysell (2018)
The purpose of this research work is to determine the incidence of the implementation of an internal control system in the contracting body of the Network of Health Trujillo- 2017 period. For this purpose, an evaluation was made of the organic structure and the procedures performed, by the Logistics Unit, in order to identify the weaknesses of the unit that can generate a deficient management of public resources and the fulfillment of goals and objectives of the entity. The type of research carried out in this thesis is descriptive, allowing to collect information on each of the variables without altering or modifying the data obtained, the population is constituted by the Network of Health Trujillo, the sample is constituted by the Logistics Unit as Contracting Organ of Trujillo Health Network; In addition, historical information was considered from previous exercises and statistics on beneficiaries of goods and services provided by the entity. It was concluded that the implementation of an internal control system to the Contracting Body, will maximize the financial resources of the entity, however to achieve an integral development of the management, the implementation of the internal control system should be applied to each and every one of the units, offices and areas that make up the entity.